Learning, unlearning and relearning - Abd Razak, Dzulkifli (2009)
IT had been a successful 5th World Environment Education Congress that ended in Montreal last week. What started as a small gathering of a concerned group of 350 people on the state of the world environment in Espinho, Portugal, in 2003, drew more than 2,000 participants, representing virtually all disciplines and activities, in Montreal. It has gained momentum as a social movement, registering its presence in matters about the environment, and, at the same time calling to question what has gone terribly wrong.